The Place of Translation in Nigerian Cultural Diplomacy and its Impact on Translation Exchanges - Madueke, Sylvia (TTR)

(untitled) (Association canadienne de traductologie, 2019)
This paper focuses on the translation of Nigerian literature into French from the perspective of cultural diplomacy and as a cultural product (Flotow, 2007; Córdoba Serrano, 2013). It reviews Nigerian cultural diplomacy initiatives to determine if translation is highlighted as part of cultural export and as a means through which the Nigerian image and culture are promoted. Even though translation exchanges are not promoted by the Nigerian government, there is a field of translation of Nigerian texts into French. Data from a list of Nigerian novels translated into French between 1953 and 2017 provide contextual and historical information on the circulation of translations as well as on the works that are selected for translation into French.